RANCANG BANGUN SISTEM PENGATURAN PENETRALISIR KEASAMAN AIR LIMBAH RUMAH TANGGA - Hendryono Saputra; Nazori A Z; Eka Purwa Laksana; Suwasti Broto; Indra Riyanto (MAESTRO, 2022)
Neutralizing household wastewater into clean water is currently one way to reduce groundwater use. In this final project, a neutralization system will be designed for residential wastewater into clean water. This system consists of, water level sensor, water ph sensor, microcontroller, pump, . Wastewater from each house is channeled into a holding tank. If the waste water reservoir is full and the clean water reservoir is empty, the wastewater from the reservoir is channeled into a water treatment tank to be processed into clean water with a pH value of 7 to 9. achieved. Meanwhile, if the waste water reservoir is full and the clean water reservoir is also full, the clean water can be channeled for the needs of the residents or flowed into the river. With this concept, residents' need for clean water from ground water can be reduced and the water discharged into the river is also clean water that does not pollute the river. The energy source for power supply to the system comes from solar energy which is stored using batteries. The process of neutralizing wastewater with injection / addition of aluminum sulfate / alum (Al2OH) and aluminum chloride (PAC) as much as 9 mL is able to raise the pH from 4.3 to 7.81 so the results have met the water quality standard.